2019
DOI: 10.3389/fnagi.2019.00203
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the MotionWatch8©: Calibrating Cut-Points for Measuring Physical Activity and Sedentary Behavior Among Adults With Stroke

Abstract: Reduced moderate-to-vigorous physical activity (MVPA) and increased sedentary behavior (SB) are common following stroke, which can limit stroke recovery and contribute to greater cognitive decline. Hence, the MVPA and SB of adults with stroke should be measured concurrently using objective methods. One currently available method for objectively measuring MVPA and SB is the MotionWatch8© (MW8). However, adults with stroke can have significant mobility restrictions (depending on stroke severity) and thus it is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
0
8
1
Order By: Relevance
“…Differentiation of sedentary from light activity was much greater in the study by Lin et al (45), given the much lower sedentary threshold score (SED < 32 counts/30s) compared to the present study (SED < 215 counts/30s, MOA < 118 counts/30s). This is likely related to Lin et al (45) prioritizing higher specificity at the cost of lower sensitivity in order to minimise false positives due to arm movements. Johansson et al (12) used the opposite adjustment -towards higher sensitivity at the expense of a lower specificity for the SED threshold in order to avoid underestimating the time spent in SED.…”
Section: The Observation Technique (Video During Free Play Of Groups ...contrasting
confidence: 77%
See 2 more Smart Citations
“…Differentiation of sedentary from light activity was much greater in the study by Lin et al (45), given the much lower sedentary threshold score (SED < 32 counts/30s) compared to the present study (SED < 215 counts/30s, MOA < 118 counts/30s). This is likely related to Lin et al (45) prioritizing higher specificity at the cost of lower sensitivity in order to minimise false positives due to arm movements. Johansson et al (12) used the opposite adjustment -towards higher sensitivity at the expense of a lower specificity for the SED threshold in order to avoid underestimating the time spent in SED.…”
Section: The Observation Technique (Video During Free Play Of Groups ...contrasting
confidence: 77%
“…In Johansson et al (12), authors argued for age-specific thresholds since they found that 4-year-old preschool children, who wore a GT3X triaxial on their non-dominant wrist, produced generally higher intensity thresholds per 5s-epoch in comparison to toddlers of 2 years (19). Differentiation of sedentary from light activity was much greater in the study by Lin et al (45), given the much lower sedentary threshold score (SED < 32 counts/30s) compared to the present study (SED < 215 counts/30s, MOA < 118 counts/30s). This is likely related to Lin et al (45) prioritizing higher specificity at the cost of lower sensitivity in order to minimise false positives due to arm movements.…”
Section: The Observation Technique (Video During Free Play Of Groups ...mentioning
confidence: 97%
See 1 more Smart Citation
“…Accelerometry is a non‐invasive method for monitoring PA. Patients were instructed to wear the accelerometer (MotionWatch8®, Camntech, Cambridge, UK) 19,20 wristband continuously during the study. Assessment of PA was performed during the entire duration of the study (from Week −2 to Week 12) using a continuously wrist‐worn accelerometry device on non‐dominant wrist.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that inadequate levels of PA of at least moderate intensity are a significant risk factor for recurrent stroke and that sitting time is an independent risk factor for cardiovascular disease-related mortality [ 9 , 13 ], public health programs and policies in chronic stroke should prevent physical inactivity and SB [ 4 ]. In this sense, to change these behaviors, it is critical to know the modifiable factors associated with them in people with sequelae of chronic stroke [ 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%